US food security and climate change: agricultural futures - Takle ES; Gustafson D; Beachy, Roger N.; Nelson, Gerald C.; Mason-D'Croz, Daniel; Palazzo, Amanda (ZBW - German National Library of Economics, 2013)
Agreement is developing among agricultural scientists on the emerging inability of agriculture to meet growing global food demands. Changes in trends of weather conditions projected by global climate models will challenge physiological limits of crops and exacerbate the global food challenge by 2050. These climate- and constraint-driven crop production challenges are interconnected within a complex global economy, where diverse factors add to price volatility and food scarcity. Our scenarios of the impact of climate change on food security through 2050 for internationally traded crops show that climate change does not threaten near-term US food security due to the availability of adaptation strategies. However, as climate continues to change beyond 2050 current adaptation measures will not be sufficient to meet growing food demand. Climate scenarios for higher-level carbon emissions exacerbate the food shortfall, although uncertainty in projections of future precipitation is a limitation to impact studies.